Pengenalan dan Pelatihan Biosaka sebagai Elisitor Tanaman pada Kelompok Tani Desa Sukosari, Kec. Kasembon, Kab. Malang - Mohamad Alvin Fauzi; Mujahidin Ahmad; Eva Apriliana; Afifah Agil Ningtyas (JRCE (Journal of Research on Community Engagement), 2026)
Agriculture is one of the jobs that supplies all the needs of the Indonesian people. Indonesian agriculture still uses a lot of chemical pesticides to support the growth period of agricultural crops. Biosaka elicitor is a product made from plant extracts which is neither a fertilizer nor a pesticide. The use of biosac elicitors as a substitute for pesticides is still not maximized due to the lack of knowledge of farmers about biosac elicitors. Counseling and training on biosac elicitors is the first step to provide knowledge to farmers to switch from chemical pesticides to organic pesticides. Biosaka elicitor contains phytoalexins which can increase plant metabolism so that they become more resistant to disease